Fatigue Life and Surface Hardening Investigation of Aluminum Shot Peening Process - Kayser Ameen (Engineering and Technology Journal, 2018)
Two different tests are used in order to analyze the shot peening foraluminum 6061-T6 alloys. Stress amplitude versus fatigue life (S-N curves) are established experimentally using different shot peening ball size (three diameters of balls are used in this paper are 1.5, 3, and 3.5 mm). Also the hardening via Vickers hardnessis evaluated due to shot peening experimentally and by ANSYS software, the three dimensional finite element model of a square plate shot by ball is demonstrates the application of shot peened of hardening surface.The influences of the ball’s diameter on the hardening and S-N curves are studied. The results showed that the fatigue strength is increased when increasing the ball diameter. The higher strength was obtained when using the ball diameter of (3.5 mm) compared to the other diameters (1.5 and 3 mm). Good agreement of hardening results is evident between experimental and Ansys results with average discrepancy 3.6%